A Journal PELATIHAN DIGITAL PUBLIC SPEAKING DHAMMADESANA PARA SAMANERA DAN ATTHASILANI - Robi Sugara Robi Sugara (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
Digital Public Speaking is a technique of speaking in front of a camera lens to a group of people in a structured manner with the aim of providing information and influencing the listening audience. The aims of this study are: 1) to determine the implementation of Digital Public Speaking Training for Samanera and Atthasilani at Padepokan Dhammadipa Arama Batu; 2) to find out the impact of Digital Public Speaking Training on Samanera and Atthasilani at Padepokan Dhammadipa Arama Batu. This research analysis research using Miles and Huberman's version. The sample used was 6 respondents consisting of 3 Samanera and 3 Atthasilani. The sample in this study was conducted by means of interviews, observation, and documentation. The results of the study indicate that: (1) the Digital Public Speaking ability of Samanera and Atthasilani at Padepokan Dhammadipa Arama Batu. The conclusion is that the ability to preach digitally has begun to increase but it is stillnot in accordance with the 3T method (regular, structured, and measurable).